2023
DOI: 10.1089/jpm.2022.0277
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Burden and Shared Care Planning in an Oncology Nurse-Led Primary Palliative Care Intervention (CONNECT) for Patients with Advanced Cancer

Abstract: Purpose: Primary Palliative Care (PPC) interventions are needed to address unmet symptom needs within standard oncology care. We designed an oncology nurse-led PPC intervention using shared care planning to facilitate patient engagement. This analysis examines the prevalence and severity of symptoms reported by patients and how symptoms were addressed on shared care plans.Methods: Secondary analysis of a cluster randomized PPC intervention trial. Adult patients with metastatic solid tumors whose oncologist 'wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Patients in need of palliative care have a range of different symptoms and concerns such as pain, anxiety, dyspnea, depression, anxiety, social and spiritual distress (Bandeali et al, 2020 ). A study of patients with metastatic cancer found that the most prevalent and severe self‐reported symptoms were tiredness, low sense of well‐being, and poor appetite (Mitchell et al, 2022 ). Patients receiving specialized palliative care also describe experiencing existential loneliness (Sjöberg et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients in need of palliative care have a range of different symptoms and concerns such as pain, anxiety, dyspnea, depression, anxiety, social and spiritual distress (Bandeali et al, 2020 ). A study of patients with metastatic cancer found that the most prevalent and severe self‐reported symptoms were tiredness, low sense of well‐being, and poor appetite (Mitchell et al, 2022 ). Patients receiving specialized palliative care also describe experiencing existential loneliness (Sjöberg et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…
Patients with progressive incurable disease should have access to palliative care services, which proactively detect and address the problems of their conditions and the effect these problems have on them and their families (World Health Organization[WHO], 2020). Here, we use the term 'family' in its broadest sense, to include all persons who are significant to the patients.Patients in need of palliative care have a range of different symptoms and concerns such as pain, anxiety, dyspnea, depression, anxiety, social and spiritual distress (Bandeali et al, 2020).A study of patients with metastatic cancer found that the most prevalent and severe self-reported symptoms were tiredness, low sense of well-being, and poor appetite (Mitchell et al, 2022).Patients receiving specialized palliative care also describe experiencing existential loneliness (Sjöberg et al, 2017). Specialized palliative care is provided by specialists for seriously ill patients with complex problems (Payne et al, 2022).
…”
mentioning
confidence: 99%
See 1 more Smart Citation